Energy flexibility analysis of office building using pre-cooling with structural thermal mass. Issue 5 (September 2019) - Lu, Fei; Yu, Zhenyu; Yang, Xudong; Zou, Yu
Abstract: The increasing share of renewable energy sources (RES) increases the imbalance between supply and demand, due to its fluctuation and intermittence. Eenergy flexible buildings are proposed as an important part of the solution to balance supply and demand. However, the thermal storage of a building is not utilized for reducing the considerable peak-to-valley difference in conventional night setup control strategies. In this context, pre-cooling is the most commonly used approach for charging cooling in building thermal mass to achieve energy flexibility. The objective of this paper is to assess the building flexibility potential using pre-cooling with structural thermal mass. We proposed quantitative indexes including valley-filling capacity, peak-shaving capacity and energy-shifting efficiency based on the improvement of existing indicators according to previous research. As considering the impact of structural thermal mass, heat transfer coefficient, pre-cooling duration, pre-cooling temperature on energy flexibility, a total of 35 scenarios are simulated using TRNSYS and evaluated using the quantitative indexes. Finally, the results may supply suggestions to utilize building energy flexibility with pre-cooling and optimize the corresponding control strategy.